EVALUATION OF THE CENTRAL REGION OF MARICÁ FROM THE PERSPECTIVE OF DEVELOPMENT ORIENTED TO PUBLIC TRANSPORT – DOT - Gomes , Maria Vitória Ribeiro; Ávila, Giovani Manso (Seven Editora, 2024)
This article aims to evaluate the central region of the municipality of Maricá - RJ, from the perspective of Public Transport-Oriented Development - DOT (ITDP, 2024). A territorial cut in the Municipality of Maricá will be presented from the perspective of the five characteristics of the DOT (VTPI, 2019). It is expected to survey the advances in urban mobility, which this city can offer as an example to other Brazilian cities, as well as identify the weak points to be mitigated. The article concludes that the five characteristics of the DOT are partially met in Maricá. It is recommended that future studies evaluate the contrast present in the central region with the other neighborhoods, which have lower population density and less urban attractions. It is expected that this research will encourage the application of the DOT concept in cities, increasing traffic quality and sustainability. DOI:https://doi.org/10.56238/sevened2024.037-018